Binder, negative pole piece and secondary battery

By using a binder prepared in combination with guar gum, aromatic sulfonate polymer, polyether compound and graphene oxide, the problem of decreasing adhesion of lithium-ion battery binder under high temperature conditions is solved, and the problem of decreasing adhesion of lithium-ion battery binder under high temperature conditions is achieved. The ratio and circulation performance of lithium-ion batteries have improved, extending battery life.

CN119307195AActive Publication Date: 2025-01-14SHENZHEN HAODYNE TECH CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411833326.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-01-14
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

The existing lithium-ion battery binder reacts with metal lithium or lithiated carbon materials under high temperature conditions, resulting in a decrease in adhesion between the electrode material and the current collector, affecting the fast charging performance, and lacking ion transmission capabilities, limiting the battery's Magnification and cycling performance.

Method used

The binder prepared by combining guar gum, aromatic sulfonate polymer, polyether compound and graphene oxide has excellent ion conduction and electron conduction functions, improves bonding strength and stability, and is suitable for negative electrodes. Pole plate and secondary battery.

Benefits of technology

It significantly improves the rate performance and cycling performance of lithium-ion batteries, extends the service life of the battery, and maintains the stability and conductivity of the electrode structure under high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of battery materials, in particular to a binder, a negative pole piece and a secondary battery, and the binder comprises guar gum, an aromatic sulfonate polymer, a polyether compound and graphene oxide. The binder provided by the invention has relatively high peel strength and good ion conduction and electron conduction functions, and is very beneficial for improving the rate capability and cycle performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a binder, a negative electrode sheet and a secondary battery. Background Art

[0002] As an efficient energy storage solution, lithium-ion batteries are widely used in electric vehicles (EVs), plug-in hybrid electric vehicles (PHEVs) and portable electronic devices due to their advantages such as high energy density, low cost, excellent safety and long cycle life.

[0003] As the application scenarios of lithium batteries continue to expand, users' demand for fast charging is growing, which has prompted researchers to focus on improving the speed of ion and electron transmission in lithium-ion batteries during the charging and discharging process.

[0004] In practical applications, the working efficiency of lithium-ion batteries not only depends on the characteristics of the active material itself, but also is affected by the migration rate of lithium ions between different media during the charging and discharging process.

[0005] Specifically, lithium ions must pass through multiple links, including the interior of the electrode active material's grains, grain boundaries, and the contact surfaces between the particle surface and the binder, conductive agent, and electrolyte, to complete the entire charging and discharging process.

[0006] The slow migration of lithium ions between solid materials and their interfaces has become the main bottleneck restricting the dynamic performance of batteries.

[0007] Therefore, accelerating the movement of lithium ions within solid materials and between interfaces is one of the key measures to improve the overall performance of lithium-ion batteries.

[0008] Binders play an important role in lithium-ion batteries by connecting active materials with conductive agents and fixing them on the current collector. They not only help maintain the structural stability of the electrode, but also adapt to the volume changes of the electrode material during the charging and discharging process, which is crucial to extending the service life of the battery.

[0009] Although currently used binders such as polyvinylidene fluoride (PVDF) perform well in some aspects, they also have certain limitations. For example, they react with metallic lithium or lithiated carbon materials under high temperature conditions, resulting in decreased adhesion between the electrode material and the current collector, increased contact resistance, and affected fast charging performance.

[0010] Although the use of a composite binder composed of styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC) can improve the above problems to a certain extent, it also limits the battery's rate and cycle performance due to the lack of ion transmission capacity.

[0011] Polyacrylic acid (PAA) contains -COOLi / -COOH, which has certain benefits for the transmission of lithium ions. However, it has a high glass transition temperature and high hardness. The negative electrode sheets prepared by using it in negative electrode slurry are very brittle and are prone to powder loss when the electrodes are cut, affecting battery performance.

[0012] At the same time, this type of binder does not have the ability to conduct electrons, which is not conducive to improving the rate performance of lithium batteries.

[0013] Therefore, it is of great significance to develop a binder with ion conduction and electron conduction functions for use in negative electrode sheets and secondary batteries. Summary of the invention

[0014] In order to solve the above technical problems, the present invention provides a binder, a negative electrode plate and a secondary battery.

[0015] The adhesive provided by the invention has excellent peel strength and is very beneficial to improving the rate performance and cycle performance of the battery.

[0016] In a first aspect, the present invention provides a binder comprising guar gum, a polymer of aromatic sulfonate, a polyether compound and graphene oxide.

[0017] In the present invention, by using guar gum, a polymer of aromatic sulfonate, a polyether compound and graphene oxide in combination, the prepared binder has good ion conduction and electron conduction functions and has high bonding strength.

[0018] Preferably, the solid content of the binder is 8wt%-20wt%.

[0019] In the present invention, the solid content of the binder is adjusted by deionized water.

[0020] Preferably, the swelling degree of the binder is less than 5%, for example, 5%, 4%, 3%, 2%, 1%. In the present invention, the swelling degree of the binder can be adjusted by adjusting the content of each component in the binder and the viscosity of guar gum, the viscosity and molecular weight of polyethylene oxide.

[0021] The binder provided by the present invention has a low swelling degree, which ensures that the binder will not swell in the electrolyte, and helps to maintain the stability of the electrode structure.

[0022] The viscosity of the binder is 5000-30000 mPa.s, preferably 8000-15000 mPa.s.

[0023] Specifically, for example, it may be 6000 mPa.s, 7000 mPa.s, 8000 mPa.s, 9000 mPa.s, 10000 mPa.s, 11000 mPa.s, 12000 mPa.s, 13000 mPa.s, 14000 mPa.s, 15000 mPa.s, 16000 mPa.s, 18000 mPa.s, 20000 mPa.s, 25000 mPa.s, 28000 mPa.s, or 30000 mPa.s.

[0024] In the present invention, the viscosity of the binder can be adjusted by adjusting the content of each component in the binder and the viscosity of guar gum, the viscosity and molecular weight of polyethylene oxide.

[0025] In the present application, the adhesive within this solid content range and viscosity range has moderate viscosity, which is neither too thin nor too thick, so that the adhesive has good fluidity and can better fill and penetrate into the surface micropores of the adherend, thereby improving the bonding effect. In addition, the polymer and graphene oxide in the adhesive can be fully cross-linked to form a dense network structure, thereby improving the bonding strength and durability.

[0026] Specifically, the solid content of the binder is tested by the following method: accurately weigh a certain amount of binder sample, record the initial weight W1, spread the sample evenly on the sample tray of the infrared dryer, set the appropriate temperature and time for drying according to the instrument manual, take the dried sample out of the infrared dryer, put it in a dryer and cool it to room temperature. After cooling, accurately weigh the dried sample weight W2, solid content (%) = (W2 / W1) × 100.

[0027] Specifically, the viscosity of the adhesive is tested using the following method: pour the adhesive sample to be tested into a clean sample cup, ensure that the sample volume is sufficient to cover the rotor of the viscometer, turn on the rotational viscometer, select a medium-sized rotor and a moderate rotation speed (such as 60 rpm), slowly immerse the rotor in the sample, ensure that the rotor is completely immersed and there are no bubbles, start the viscometer, record the viscosity value, perform multiple measurements and take the average value.

[0028] In this application, guar gum is a natural polysaccharide with excellent adhesion and film-forming properties.

[0029] It can form a close contact with the surface of the electrode collector and improve the initial adhesion of the adhesive.

[0030] Preferably, the viscosity of a 1% aqueous solution of the guar gum is 500-5000 mPa.s; and / or the hydroxyl content of the guar gum is not less than 97%.

[0031] When the viscosity of the 1% aqueous solution of the guar gum (i.e. the viscosity of the aqueous solution with a guar gum concentration of 1%) is 500-5000 mPa.s, it is very beneficial to improve the stability of the adhesive and improve the bonding strength.

[0032] In the present invention, the viscosity of the 1% aqueous solution of guar gum is further preferably 1000-4500 mPa.s, specifically, for example, it can be 1000 mPa.s, 1200 mPa.s, 1500 mPa.s, 1800 mPa.s, 2000 mPa.s, 2500 mPa.s, 3000 mPa.s, 3500 mPa.s, 4000 mPa.s, 4500 mPa.s, or 5000 mPa.s.

[0033] The hydroxyl content of the guar gum is not less than 97%, and more preferably the hydroxyl content of the guar gum is 97-99%.

[0034] At this time, the hydroxyl content in guar gum is high, and it can form a large number of hydrogen bonds with the negative electrode active materials (such as graphite, silicon, etc.), which is very beneficial to further maintain the stability of the electrode structure, and is also beneficial to improving the ionic conductivity of the binder.

[0035] The above guar gum is commercially available.

[0036] Preferably, the hydroxyl content of the graphene oxide is 10-15wt%; and / or the single-layer sheet diameter of the graphene oxide is 0.5-10 μm.

[0037] In the present invention, the hydroxyl content of graphene oxide is within the above range, and can be more effectively physically cross-linked with other components through hydrogen bonds, thereby transforming the linear binder into a three-dimensional structure, significantly improving the mechanical strength of the binder.

[0038] In a further preferred embodiment, the hydroxyl content of the graphene oxide is 11-14wt%. Moreover, when the single-layer sheet diameter of graphene oxide is 0.5-10 μm, it is beneficial to improve the electrochemical performance of the battery.

[0039] Specifically, in the present invention, the above-mentioned graphene oxide can provide a large number of ion transmission channels, which not only increases the diffusion path of lithium ions, but also reduces the resistance in the ion transmission process, thereby significantly improving the transmission efficiency of lithium ions. It is suitable for negative electrode sheets or secondary batteries, and can complete the charging and discharging process in a shorter time, thereby improving the speed and efficiency of energy conversion.

[0040] The introduction of the above-mentioned graphene oxide can effectively improve the stability of the electrode interface. The hydroxyl functional groups on the surface of graphene oxide can form stable chemical bonds with the electrode material, preventing the electrode material from peeling off and dissolving during the charge and discharge process, thereby extending the cycle life of the battery.

[0041] In addition, the high conductivity of graphene oxide itself helps to reduce interfacial resistance and further improve electrochemical performance.

[0042] And, secondly, as a two-dimensional nanomaterial, graphene oxide has excellent thermal conductivity and high temperature resistance. The introduction of graphene oxide effectively improves the thermal stability of the binder.

[0043] When graphene oxide is dispersed in the binder, it can construct an effective heat conduction path, accelerate the dissipation of heat, reduce the occurrence of local overheating, and thus extend the service life of the binder.

[0044] Graphene oxide also gives the binder better chemical stability and corrosion resistance.

[0045] The rich hydroxyl active groups on its surface can prevent harmful substances from corroding the internal structure of the adhesive to a certain extent, protect the bonding parts from the influence of external environmental factors, and improve the stability of the adhesive.

[0046] The polyether compound includes polyethylene oxide.

[0047] Polyethylene oxide (PEO) is a high molecular weight polymer with good hydrophilicity and adhesion. PEO can increase the wettability and fluidity of the adhesive and improve the bonding strength.

[0048] Preferably, the weight average molecular weight of the polyether compound is 700,000-1,000,000; and / or the viscosity of the polyether compound is 9,000-18,000 mPa.s.

[0049] The aromatic sulfonate polymer includes polystyrene sulfonate.

[0050] The sulfonic acid groups in polystyrene sulfonate not only provide good ionic conductivity but also enhance the mobility of lithium ions in the electrolyte by forming stable transmission channels.

[0051] This characteristic is crucial to improving the battery's charge and discharge efficiency and cycle life.

[0052] The presence of sulfonic acid groups also facilitates the dissociation of lithium ion pairs in the electrolyte, ensuring that lithium ions can migrate quickly and efficiently from one location to another, a process known as "hopping transport."

[0053] Specifically, the polystyrene sulfonate may be existing lithium polystyrene sulfonate (CAS: 9016-91-5) and / or sodium polystyrene sulfonate.

[0054] The binder provided by the invention comprises guar gum, polystyrene sulfonate, polyethylene oxide and graphene oxide.

[0055] Guar gum is rich in polyhydroxy structures and can form a large number of hydrogen bonds with the surface of negative electrode active materials, which helps to maintain the stability of the electrode structure.

[0056] In addition, it also has good ionic conductivity.

[0057] Polyethylene oxide has excellent electronic conductivity and can form hydrogen bonding interactions with guar gum. This interaction reduces the solubility of polyethylene oxide in the electrolyte, reduces its crystallinity, and thus enhances the ionic conductivity.

[0058] Moreover, a three-dimensional network structure is constructed through the hydrogen bonding between polyethylene oxide and guar gum, which not only increases the binding sites between negative electrode active materials such as graphite or silicon and the binder, but also effectively alleviates the stress generated during the volume change process.

[0059] Graphene oxide contains abundant hydroxyl functional groups, which can be physically cross-linked with other components in the binder through hydrogen bonds, thereby transforming the linear binder into a three-dimensional structure, significantly improving the mechanical strength of the binder.

[0060] At the same time, guar gum and polyethylene oxide both have certain ion conductivity, and the negatively charged sulfonic acid groups provide a stable transmission path for lithium ions, promote the dissociation of ion pairs in the electrolyte, and accelerate the movement of lithium ions.

[0061] Under this mechanism, lithium ions can achieve rapid and stable migration by "jumping" between adjacent sulfonic acid groups under the action of the electric field, thereby improving the migration efficiency.

[0062] After adding graphene oxide, the binder acquires the ability to conduct both electrons and ions, which is very beneficial for improving the rate performance of electrode materials.

[0063] Preferably, in the binder, the mass ratio of guar gum, polyether compound, aromatic sulfonate polymer and graphene oxide is (30-40): (30-40): (10-20) (10-30).

[0064] In a second aspect, the present invention provides a negative electrode plate, wherein the negative electrode plate comprises the binder provided in the first aspect.

[0065] Preferably, the peel strength of the negative electrode sheet is greater than 10 N / m.

[0066] In the present application, when the peel strength of the negative electrode sheet is greater than 10 N / m, the bond between the negative electrode material and the current collector is made stronger.

[0067] During the battery charging and discharging process, even if encountering temperature changes or mechanical shocks, it can effectively prevent the negative electrode material from falling off, thereby reducing the risk of internal short circuit and improving the overall safety of the battery; good peel strength is conducive to ensuring the stability of the battery's electrochemical performance during the cyclic charging and discharging process.

[0068] When the peel strength of the negative electrode sheet is greater than 10N / m, it can also ensure that the electron transmission path is unobstructed, thereby improving the energy density and power density of the battery, so that the battery can still maintain an efficient working state under high-rate charge and discharge conditions.

[0069] Preferably, the negative electrode plate further includes a negative electrode active material, a negative electrode conductor, and an auxiliary binder.

[0070] Preferably, the negative electrode active material is selected from one or more of graphite, silicon oxide, and silicon carbon, the negative electrode conductive agent is selected from one or more of conductive carbon black, carbon nanotubes, polyaniline, and polypyrrole, and the auxiliary binder is selected from one or more of sodium carboxymethyl cellulose and polyacrylic acid.

[0071] In the present invention, the negative electrode active material is preferably graphite, the negative electrode conductive agent is preferably conductive carbon black, and the auxiliary binder is preferably sodium carboxymethyl cellulose.

[0072] In the present application, graphite, as the main active material, can effectively store and release lithium ions, thereby improving the energy density of the battery. The layered structure of graphite is conducive to the embedding and de-embedding of lithium ions, reducing the irreversible capacity loss, and helping to extend the cycle life of the battery; conductive carbon black has excellent conductive properties, can form an effective conductive network, improve the overall conductivity of the negative electrode material, accelerate the transmission speed of lithium ions and electrons, and improve the high current charge and discharge capacity of the battery. At the same time, conductive carbon black helps the performance of the battery under high rate charge and discharge conditions, allowing the battery to be quickly charged or discharged in a short time without losing too much capacity; sodium carboxymethyl cellulose can provide good dispersibility and stability when preparing the negative electrode slurry, avoiding sedimentation or stratification of the slurry during stirring, and the film formed by sodium carboxymethyl cellulose can effectively inhibit the dissolution and shedding of the active material, reduce the formation and destruction of the SEI film (solid electrolyte interface film), thereby improving the cycle stability and service life of the battery.

[0073] Preferably, the mass ratio of the binder, the negative electrode active material, the negative electrode conductive agent, and the auxiliary binder is (0.5-2.0): (95-97.7): (1-1.5): (0.8-1.5).

[0074] In a third aspect, the present invention further provides a secondary battery, wherein the secondary battery comprises a negative electrode sheet according to the second aspect.

[0075] In the present application, the method for preparing a secondary battery comprises the following steps: The preparation method of the binder comprises the following steps: S1. According to the mass ratio of guar gum, polyether compound, aromatic sulfonate polymer and graphene oxide of (30-40): (30-40): (10-20) (10-30), weigh guar gum, polyether compound, aromatic sulfonate polymer and graphene oxide, add guar gum, polyether compound and deionized water into an electric stirrer and stir to form a glue solution; S2. After the preparation of the glue solution, graphene oxide and aromatic sulfonate polymer are added, and high-speed stirring is continued to disperse evenly; S3: Deionized water is added to adjust the solid content and viscosity of the glue solution to obtain a binder.

[0076] The method for preparing a negative electrode sheet comprises the following steps: S11, weighing the components according to the mass ratio of binder, graphite, conductive carbon black and sodium carboxymethyl cellulose: (0.5-2.0): (95-97.7): (1-1.5): (0.8-1.5); S12, put the weighed graphite, conductive carbon black and CMC into a stirrer, add deionized water and stir evenly, add the binder solution, and continue stirring until a uniform slurry is formed; S13, evenly coating the mixed slurry on the copper foil current collector, controlling the coating thickness, and ensuring that the thickness of the negative electrode sheet after coating is uniform; S14. Place the coated negative electrode sheet in a drying oven and dry it at a certain temperature to remove excess moisture.

[0077] The drying temperature is usually 100°C and the drying time is 2 hours.

[0078] A method for preparing a secondary battery comprises the following steps: S21, putting the weighed positive electrode active material, conductive agent and binder into a stirrer, adding a solvent, and stirring until a uniform slurry is formed; S22, evenly coating the mixed slurry on the aluminum foil current collector, controlling the coating thickness to ensure that the thickness of the positive electrode sheet after coating is uniform; S23. Place the coated positive electrode sheet in a drying oven and dry it at a certain temperature to remove excess moisture.

[0079] The drying temperature is usually 100°C and the drying time is 2 hours.

[0080] S24, dissolving the electrolyte salt in the solvent and stirring evenly to obtain an electrolyte solution; S25. Stack the prepared negative electrode sheet, positive electrode sheet and separator in order, ensure that there is a separator between the positive and negative electrode sheets, put the stacked battery cells into the battery case, inject electrolyte, seal and vacuum package to ensure that there is no air residue inside the battery. DETAILED DESCRIPTION

[0081] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0082] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the protection scope of the present invention.

[0083] Example 1 This embodiment provides a method for preparing a binder, comprising the following steps: S1. Guar gum (1% aqueous solution has a viscosity of 531 mPa.s and a hydroxyl content of 97%), polyethylene oxide (weight average molecular weight of 700,000 and a viscosity of 9259 mPa.s), poly(4-styrene sulfonic acid) lithium salt, and graphene oxide (hydroxyl content of 10wt%, single-layer sheet diameter of 8μm) are weighed according to a mass ratio of 30:30:10:10. Guar gum, polyethylene oxide, poly(4-styrene sulfonic acid) lithium salt, and graphene oxide are added to an electric stirrer and stirred to form a glue solution; S2. After the preparation of the glue solution, add graphene oxide and poly (4-styrene sulfonic acid) lithium salt, and continue to stir at high speed to disperse evenly; S3: Deionized water is added to adjust the solid content and viscosity of the glue solution to obtain a binder.

[0084] In this embodiment, the solid content of the binder is 10 wt % and the viscosity is 5589 mPa.s.

[0085] After testing, the swelling degree of the adhesive is 5%.

[0086] The swelling degree detection method is as follows: take two containers and add electrolyte, the electrolyte is 1M LiPF6, the binder is made into a film and dried to bear weight to obtain Winitial, the film specification is a circular sheet with a diameter of 20mm and a thickness of 20μm, the polymer particles are immersed in the electrolyte, after leaving it for 72h, take it out and wipe off the electrolyte on the surface and weigh it to obtain Wbalance, swelling degree = (Wbalance-Winitial) / Winitial*100%.

[0087] The above-mentioned binder is used to prepare a negative electrode sheet, wherein the mass ratio of the binder, graphite, conductive carbon black, and sodium carboxymethyl cellulose is 2:95:1.5:1.5. The preparation method of the negative electrode sheet comprises the following steps: S11, weigh each component; S12, put the weighed graphite, conductive carbon black and CMC into a stirrer, add deionized water and stir evenly, add the binder solution, and continue stirring until a uniform slurry is formed; S13, evenly coating the mixed slurry on the copper foil current collector, controlling the coating thickness, and ensuring that the thickness of the negative electrode sheet after coating is uniform; S14. Place the coated negative electrode sheet in a drying oven and dry it at a certain temperature to remove excess moisture.

[0088] The drying temperature is usually 100°C and the drying time is 2 hours.

[0089] A method for preparing a secondary battery comprises the following steps: S21, putting the weighed positive electrode active material, conductive agent and binder into a stirrer, adding a solvent, and stirring until a uniform slurry is formed; S22, evenly coating the mixed slurry on the aluminum foil current collector, controlling the coating thickness to ensure that the thickness of the positive electrode sheet after coating is uniform; S23. Place the coated positive electrode sheet in a drying oven and dry it at a certain temperature to remove excess moisture.

[0090] Usually the drying temperature is 100℃ and the drying time is 2h; S24, dissolving the electrolyte salt in the solvent and stirring evenly to obtain an electrolyte solution; S25. Stack the prepared negative electrode sheet, positive electrode sheet and separator in order, ensure that there is a separator between the positive and negative electrode sheets, put the stacked battery cells into the battery case, inject electrolyte, seal and vacuum package to ensure that there is no air residue inside the battery.

[0091] Example 2 Compared with Example 1, the only difference is that in the preparation of the binder, the mass ratio of guar gum (1% aqueous solution has a viscosity of 1241 mPa.s and a hydroxyl content of 97%), polyethylene oxide (weight average molecular weight of 900,000 and viscosity of 11289 mPa.s), poly(4-styrene sulfonic acid) lithium salt, and graphene oxide (hydroxyl content of 15wt%, single-layer sheet diameter of 10μm) is 35:35:15:20.

[0092] In this embodiment, the solid content of the binder is 10wt% and the viscosity is 8294mPa.s.

[0093] After testing, the swelling degree of the adhesive was 4%.

[0094] Example 3 Compared with Example 1, the only difference is that in the preparation of the binder, the mass ratio of guar gum (1% aqueous solution has a viscosity of 2113 mPa.s and a hydroxyl content of 97%), polyethylene oxide (weight average molecular weight of 800,000 and viscosity of 10318 mPa.s), poly (4-styrene sulfonic acid) lithium salt, and graphene oxide (hydroxyl content of 14wt%, single-layer sheet diameter of 8μm) is 35:35:15:20.

[0095] In this embodiment, the solid content of the binder is 10 wt % and the viscosity is 9341 mPa.s.

[0096] After testing, the swelling degree of the adhesive was 4%.

[0097] Example 4 Compared with Example 1, the only difference is that in the preparation of the binder, the mass ratio of guar gum (1% aqueous solution has a viscosity of 4852 mPa.s and a hydroxyl content of 97%), polyethylene oxide (weight average molecular weight of 900,000 and viscosity of 11289 mPa.s), poly(4-styrene sulfonic acid) lithium salt, and graphene oxide (hydroxyl content of 12 wt% and single-layer sheet diameter of 4 μm) is 40:40:20:30.

[0098] In this embodiment, the solid content of the binder is 20wt% and the viscosity is 29489mPa.s.

[0099] After testing, the swelling degree of the adhesive was 1%.

[0100] Example 5 Compared with Example 1, the only difference is that in the preparation of the binder, the mass ratio of guar gum (1% aqueous solution has a viscosity of 4013 mPa.s and a hydroxyl content of 97%), polyethylene oxide (weight average molecular weight of 1 million and viscosity of 14348 mPa.s), poly(4-styrene sulfonic acid) lithium salt, and graphene oxide (hydroxyl content of 12wt% and single-layer diameter of 5μm) is 35:35:15:20.

[0101] In this embodiment, the solid content of the binder is 10wt% and the viscosity is 12215mPa.s.

[0102] After testing, the swelling degree of the adhesive was 1%.

[0103] Example 6 Compared with Example 1, the only difference is that in the preparation of the binder, the mass ratio of guar gum (1% aqueous solution has a viscosity of 1287 mPa.s and a hydroxyl content of 95%), polyethylene oxide (weight average molecular weight of 900,000 and viscosity of 11289 mPa.s), poly (4-styrene sulfonic acid) lithium salt, and graphene oxide (hydroxyl content of 8wt% and single-layer diameter of 1 μm) is 35:35:15:20.

[0104] In this embodiment, the solid content of the binder is 10 wt % and the viscosity is 8494 mPa.s.

[0105] After testing, the swelling degree of the adhesive was 4%.

[0106] Example 7 Compared with Example 1, the only difference is that in the preparation of the binder, the mass ratio of guar gum (1% aqueous solution has a viscosity of 380 mPa.s and a hydroxyl content of 98%), polyethylene oxide (weight average molecular weight of 500,000 and viscosity of 6418 mPa.s), poly (4-styrene sulfonic acid) lithium salt, and graphene oxide (hydroxyl content of 15wt%, single-layer sheet diameter of 0.5μm) is 30:30:10:10.

[0107] In this embodiment, the solid content of the binder is 10 wt % and the viscosity is 4231 mPa.s.

[0108] After testing, the swelling degree of the adhesive is 5%.

[0109] Comparative Example 1 Compared with Example 2, the only difference is that graphene oxide is not added in the preparation of the binder, and the remaining steps are the same as Example 2.

[0110] Comparative Example 2 Compared with Example 2, the only difference is that guar gum is not added in the preparation of the binder, and the other steps are the same as Example 2.

[0111] Comparative Example 3 Compared with Example 2, the only difference is that polyethylene oxide is not added in the preparation of the binder, and the remaining steps are the same as Example 2.

[0112] Comparative Example 4 Compared with Example 2, the only difference is that no poly(4-styrenesulfonic acid) lithium salt is added in the preparation of the binder, and the remaining steps are the same as Example 2.

[0113] Comparative Example 5 Compared with Example 2, the only difference is that the binder in Example 2 is replaced by PAA. The remaining steps are the same as Example 2.

[0114] Comparative Example 6 Compared with Example 2, the only difference is that the binder in Example 2 is replaced by SBR, and the remaining steps are the same as Example 2.

[0115] The negative electrode sheet peeling strength test was performed on each embodiment and comparative example; Negative electrode peel strength test: An electronic tensile testing machine was used to test the electrode interface peel strength, with a tensile angle of 180°, a tensile rate of 50 mm / min, and a unit of N / m. The test results are shown in Table 1.

[0116] The battery cycle performance test was carried out on each embodiment and comparative example. The battery was charged to 4.5V at a constant current of 3000mA (1C) at 25°C, then charged at a constant voltage with a cut-off current value of 150mA, and then discharged to 3V at a constant current of 3000mA, which was considered one cycle. After repeating this process 500 times, the capacity retention rate after 500 cycles (%) was calculated as (discharge capacity after 500 cycles / initial discharge capacity) × 100%. The test results are shown in Table 1.

[0117] Table 1

[0118] It can be seen from the test results in Table 1 that the binder provided by the present invention has excellent peel strength and is very beneficial to improving the rate performance and cycle performance of the battery.

[0119] Specifically, by comparing the test results of Examples 1-7 and Comparative Examples 1-4, it can be seen that when only any three components of the adhesive provided by the present invention are used, the peel strength, rate performance and cycle performance of the adhesive are significantly reduced.

[0120] By comparing the test results of Example 2 and Example 6, it can be seen that when the hydroxyl content of guar gum and graphene oxide is within the preferred range of the present invention, it is very beneficial to further improve the peel strength, rate performance and cycle performance of the adhesive.

[0121] By comparing the test results of Example 2 and Example 6, it can be seen that when the viscosity and molecular weight of guar gum and graphene oxide are within the preferred range of the invention, it is very beneficial to further improve the peel strength, rate performance and cycle performance of the adhesive.

[0122] The present invention is further described above with the aid of specific embodiments. However, it should be understood that the specific description here should not be construed as limiting the essence and scope of the present invention. Various modifications made to the above embodiments by ordinary technicians in the field after reading this specification are all within the scope of protection of the present invention.

Claims

1. A binder, characterized in that: The binder includes guar gum, a polymer of aromatic sulfonate, a polyether compound and graphene oxide.

2. The adhesive according to claim 1, characterized in that The solid content of the binder is 8wt%-20wt%; and / or the viscosity of the binder is 5000-30000 mPa.s.

3. The adhesive according to claim 1, characterized in that The polymer of the aromatic sulfonate includes polystyrene sulfonate; and the polyether compound includes polyethylene oxide.

4. The adhesive according to any one of claims 1 to 3, characterized in that The viscosity of the 1% aqueous solution of the guar gum is 500-5000 mPa.s; And / or, the hydroxyl content of the guar gum is not less than 97%.

5. The adhesive according to any one of claims 1 to 3, characterized in that: The hydroxyl content of the graphene oxide is 10-15wt%; And / or, the single-layer sheet diameter of the graphene oxide is 0.5-10 μm.

6. The adhesive according to any one of claims 3, characterized in that The weight average molecular weight of the polyethylene oxide is 700,000-1,000,000; And / or, the viscosity of the polyethylene oxide is 9000-18000 mPa.s.

7. The adhesive according to claim 1, characterized in that In the binder, the mass ratio of guar gum, polyether compound, aromatic sulfonate polymer and graphene oxide is (30-40): (30-40): (10-20) (10-30).

8. A negative electrode plate, characterized in that: The negative electrode plate comprises the binder according to any one of claims 1 to 7.

9. The negative electrode sheet according to claim 8, characterized in that: The peel strength of the negative electrode sheet is greater than 10 N / m.

10. A secondary battery, characterized in that: The secondary battery comprises the binder according to any one of claims 1 to 7 or the negative electrode sheet according to any one of claims 8 to 9.

Citation Information

Patent Citations

  • Binder for preparing lithium-sulfur soft package battery positive electrode slurry

    CN114284500A

  • Composite adhesive as well as preparation method and application thereof

    CN116589975A

  • Novel silicon negative electrode binder as well as preparation method and application thereof

    CN117903740A

  • Composite binder, preparation thereof and application of composite binder in preparation of negative electrode

    CN118496781A

  • Preparation method and application of sulfonate modified chitosan-based binder for positive electrode of lithium-sulfur battery

    CN118652642A